Disparities in the Prevalence of Malnutrition of Reproductive Women and Under Five Children in Low- and Middle- income Countries (P04-103-19) - Hasan, Md Mehedi (Curr Dev Nutr, 2019)
OBJECTIVES: To find the disparities in the prevalence of malnutrition of reproductive women and under five children. METHODS: We analyzed the latest data of nationwide cross-sectional Demographic and Health Surveys of 59 countries conducted from 2006. Between and within country gaps in malnutrition prevalence were examined. RESULTS: Undernutrition of children (stunting, wasting and underweight) and women was higher in Burundi, Madagascar, Guatemala, Yemen, Timor-Leste, India, Nigeria, Niger, Benin, Burkina Faso, Bangladesh and Ethiopia. Women's overweight was higher in Egypt, Jordan, Peru, Guatemala, Honduras, Swaziland, Dominican Republic and Bolivia. Undernutrition of women and children was higher and women's overweight was lower disproportionately among the poorest, rural and illiterate women/mother. The poor-rich gaps were greater in Guatemala, Bolivia, Burundi and Pakistan for stunting; in Cameroon, Pakistan, Niger, Yemen and Timor-Leste for wasting; and in Yemen, Pakistan, Burundi, India, Bangladesh, Nigeria and Cameroon for underweight. The greater rural-urban gaps were observed in Burundi, Peru, Bolivia, Cameroon and Mali for stunting; in Timor-Leste, Cameroon, Maldives, Niger, Guinea and Congo Democratic Republic for wasting; and in Burundi, Niger, Yemen and Cameroon for underweight. Compare to secondary + educated mother, we observed children of illiterate mothers with greater prevalence of stunting in Lesotho, Azerbaijan, Guatemala, Honduras and Bolivia; of wasting in Albania, Guyana, Tajikistan, Namibia, Nigeria and Cameroon; and of underweight in Cameroon, Pakistan and Nigeria. For women's underweight, the poor-rich gaps were greater in Yemen, Bangladesh, India, Pakistan, Kenya and Burkina Faso; the rural-urban gaps were greater in Yemen, India, Burkina Faso, Ethiopia and Pakistan; and the women's no-secondary + education gaps were greater in Kenya, Cameroon, Madagascar, Chad and Bangladesh. Higher poor-rich. rural-urban or no-secondary + education gaps in women's overweight exist in Ghana, Pakistan, Cameroon, Bangladesh, Niger, Togo, Tanzania, Kyrgyz Republic and Kenya. CONCLUSIONS: Effective nutrition interventions targeting the marginalized countries/groups may reduce the existing within and between country gaps in malnutrition. FUNDING SOURCES: None.